Toxoplasma Serostatus in Thai Free- Range Chickens: Prevalence and Two Diagnostic Methods - Ruenruetai Udonsom#; Patcharee Chaichan#; Aongart Mahittikorn; Philippe Vignoles; Aurélien Mercier; Abdelkrim Aroussi; Marie-Laure Dardé; Yaowalark Sukthana (Open Journal of Tropical Medicine - Peertechz Publications, 2017)
Toxoplasma seroprevalence in free-range chicken, which directly feed from ground, is a good indicator for detecting an environment contamination by T. gondii oocysts. Many serological methods have been used for diagnosing Toxoplasma infection in animals including chicken. Selection of appropriate methods primarily depend on their sensitivity and specificity as well as laboratory techniques, special reagent or tool requirements and regional prevalence status. The aims of this study were to determine the prevalence of T.gondii antibody in free-range chickens in Thailand and to compare two serodiagnostic methods, indirect fluorescent antibody test (IFAT) and Modified Agglutination Test (MAT). Six hundred free-range chicken sera were collected from 2 villages in Kanchanaburi Province, Thailand, 300 in 2014 and 300 in 2015. The age of chickens was between 3-6 mo, of which chickens of 2015 were older than of 2014. Collected sera were test for T. gondii IgG antibody by both methods. Over all Toxoplasma seroprevalence were 33.0% and 17.7% by IFAT and MAT, respectively. There was poor agreement between the two serological methods (kappa=0.09). IFAT in this study revealed higher positive percentage than MAT. Even though the way of living and environment in the present study was suitable for Toxoplasma transmission, the seroprevalence in Thai free-range chickens was low compared to other tropical regions such as Africa or South America. A low Toxoplasma prevalence was also found in humans, cats and other intermediate hosts in Thailand.Toxoplasmosis in Thailand causes low burden compare to other infectious diseases, however, consume well-cooked free-range chicken meat and proper practice during handling raw meat when cooking should be advocated to prevent and reduce this infection.